Moral Pancasila: A Legal Guide in Indonesia - Amalia, Nadzifah; Syaputra, Rizki; Kusuma, Nella; Dwi Sepvi Yano, Aziz; Syaputra, Rangga; Hakamulhuda, Wira; Harisval, Muhammad (Borneo Novelty Publishing, 2024)
Pancasila, as the foundation of the state and the moral guideline of the Indonesian nation, has an important role in determining the direction and principles of law in Indonesia. This literature review aims to understand the role of Pancasila as a legal guideline and how the values ​​contained therein function in the national legal system. Various previous studies indicate that Pancasila is not only an ideological foundation but also a source of norms and principles that underlie all regulations in Indonesia. In this study, Pancasila is understood as a moral guideline that includes the values ​​of humanity, unity, justice, and religion, which are expected to be the basis for every formation, application, and interpretation of law. The study includes an analysis of various references from journals, books, and relevant laws to see how Pancasila is used as a reference in the formation of legal policies. The purpose of this study is to reveal Pancasila as a legal guideline in Indonesia. This research method employs a qualitative approach, drawing from books, journals, and other relevant sources. The results of the study show that Pancasila as a guideline in the application has undergone significant changes. It should understand and apply Pancasila, Indonesia's basic law, and strengthen citizen safety and welfare. We expect this research to shed new light on the significance of Pancasila in crafting wise and beneficial laws in the modern era.